Primary epidural malignant hemangiopericytoma of thoracic spinal column causing cord compression: case report - Mohammadianpanah, Mohammad; Torabinejad, Simin; Bagheri, Mohammad Hadi; Omidvari, Shapour; Mosalaei, Ahmad; Ahmadloo, Niloofar (São Paulo Medical Journal, 2004)
CONTEXT: Hemangiopericytoma is an uncommon mesenchymal neoplasm that rarely affects the spinal canal. Primary malignant hemangiopericytoma of the spinal column is extremely rare. CASE REPORT: We report on a case of primary epidural malignant hemangiopericytoma of the thoracic spinal column that invaded vertebral bone and caused spinal cord compression in a 21-year-old man. The patient presented with progressive back pain over a four-month period that progressed to paraparesis, bilateral leg paresthesia and urinary incontinence. The surgical intervention involved laminectomy and subtotal resection of the tumor, with posterior vertebral fixation. Postoperative involved-field radiotherapy was administered. A marked neurological improvement was subsequently observed. We describe the clinical, radiological, and histological features of this tumor and review the literature.